Conservation of an Agrobacterium cT-DNA insert in Camellia section Thea reveals the ancient origin of tea plants from a genetically modified ancestor - Chen, Ke; Zhurbenko, Peter; Danilov, Lavrentii; Matveeva, Tatiana; Otten, Léon (Frontiers in Plant Science, 2022)
Many higher plants contain cellular T-DNA (cT-DNA) sequences from Agrobacterium and have been called “natural genetically modified organisms” (nGMOs). Among these natural transformants, the tea plant Camellia sinensis var. sinensis cv. Shuchazao contains a single 5.5 kb T-DNA fragment (CaTA) with three inactive T-DNA genes, with a 1 kb inverted repeat at the ends. Camellia plants are allogamous, so that each individual may contain two different CaTA alleles. 142 Camellia accessions, belonging to 10 of 11 species of the section Thea, were investigated for the presence of CaTA alleles. All accessions were found to contain the CaTA insert, showing that the Thea section derives from a single transformed ancestor. Allele phasing showed that 82 accessions each contained two different CaTA alleles, 60 others had a unique allele. A phylogenetic tree of these 225 alleles showed two separate groups, A and B, further divided into subgroups. Indel distribution corresponded in most cases with these groups. The alleles of the different Camellia species were distributed over groups A and B, and different species showed very similar CaTA alleles. This indicates that the species boundaries for the Thea section members may not be precise and require revision. The nucleotide divergence of the indirect CaTA repeats indicates that the cT-DNA insertion took place about 15 Mio years ago, before the emergence of the Thea section. The CaTA structure of a C. fangchengensis accession has an exceptional structure. We present a working model for the origin and evolution of nGMO plants derived from allogamous transformants.